PROGRAM PENGABDIAN MASYARAKAT TERPADU (PPMT) PENINGKATAN POTENSI DESA GONDANG DENGAN PEMBENTUKAN KOPERASI - lilik andriyani; Fani Riski Arbani; Faridatul Kudsiyah; Angke Diasi Iswarianti; Nur Lailia Ulinnuha; Ilma Filiana (Jurnal Abadimas Adi Buana, 2022)
The potential of Gondang Village, which has natural resources, is quite good, and most of its inhabitants are farmers. Most of the farmers in Gondang village are elderly. They experience difficulties in terms of access to long distances and access to the procurement of fertilizers, mostly subsidized fertilizers, agricultural medicines, and others, and limited knowledge of farmers. Although a small number of youth farmer groups who are members of "Taruna Tani" have not run optimally, they have not solved the problem. Another benefit of forming a cooperative is for saving money. Besides being useful for providing household consumption needs, saving money is also helpful for providing capital to meet the needs of buying fertilizers, agricultural medicines, etc. The existence of cooperatives can improve the standard of life of rural communities. The activity of forming this cooperative is to create a cooperative institution with the preparation of AD_ART, including the organizational structure of the farmer cooperative in Gondang village. The initial activity was to reactivate the farming card and BRI link. This farmer card and BRI link are handy for obtaining subsidized fertilizer and providing financial convenience.